Implementing Artificial Intelligence (International Journal of Scientific Research and Management (IJSRM), 2024)
Artificial Intelligence is about knowing something (having a knowledge) and then using that knowledge to do something with that knowledge [1]. This is demonstrated by algorithms in machine learning and data mining [1].